Oral administration of a chimeric Hepatitis B Virus S/preS1 antigen produced in lettuce triggers infection neutralizing antibodies in mice. Issue 38 (11th September 2018) - Dobrica, Mihaela-Olivia; Lazar, Catalin; Paruch, Lisa; van Eerde, André; Clarke, Jihong Liu; Tucureanu, Catalin; Caras, Iuliana; Ciulean, Sonya; Onu, Adrian; Tofan, Vlad; Branzan, Alexandru; Urban, Stephan; et al.
Highlights: A novel HBV antigen combining S and L-derived epitopes was produced in lettuce. The chimeric antigen induces humoral immune responses in orally-vaccinated mice. Antibodies elicited by the chimeric antigen are strong inhibitors of HBV infection. Abstract: Hepatitis B Virus (HBV) infection can be prevented by vaccination. Vaccines containing the small (S) envelope protein are currently used in universal vaccination programs and achieve protective immune response in more than 90% of recipients. However, new vaccination strategies are necessary for successful immunization of the remaining non- or low-responders. We have previously characterized a novel HBV chimeric antigen, which combines neutralization epitopes of the S and the preS1 domain of the large (L) envelope protein (genotype D). The S/preS1 21–47 chimera produced in mammalian cells and Nicotiana benthamiana plants, induced a significantly stronger immune response in parenterally vaccinated mice than the S protein. Here we describe the transient expression of the S/preS1 21–47 antigen in an edible plant, Lactuca sativa, for potential development of an oral HBV vaccine. Our study shows that oral administration of adjuvant-free Lactuca sativa expressing the S/preS1 21–47 antigen, three times, at 1 μg/dose, was sufficient to trigger a humoral immune response in mice. Importantly, the elicited antibodies were able to neutralize HBV infection in an NTCP-expressing infection system (HepG2-NTCP cell line) more efficiently than those induced by mice fed on Lactuca sativa expressing the S protein. These results support the S/preS1 21–47 antigen as a promising candidate for future development as an edible HBV vaccine.